Author Correction: 137 ancient human genomes from across the Eurasian steppes. (1st November 2018) - Barros Damgaard, Peter; Marchi, Nina; Rasmussen, Simon; Peyrot, Michael; Renaud, Gabriel; Korneliussen, Thorfinn; Moreno-Mayar, J.; Pedersen, Mikkel; Goldberg, Amy; Usmanova, Emma; Baimukhanov, Nurbol; Loman, Valeriy; et al.
With In this Article, Angela M. Taravella and Melissa A. Wilson Sayres have been added to the author list (associated with: School of Life Sciences, Center for Evolution and Medicine, The Biodesign Institute, Arizona State University, Tempe, AZ, USA). The author list and Author Information section have been corrected online.